ФРАЗЕОЛОГИЗМЛЕРДИҢ ГАЗЕТА ТЕМАЛАРЫ РЕТИНДЕ ҚОЛЛАНЫЎЫ - Қурбаниязов, Д. (ILIM hám JÁMIYET, 2021)
The article gives a brief overview of the study of stable phrases in the Karakalpak linguistics. The use of freezing is analyzed, the use of tropes and stylistic figures on a newspaper headline is analyzed. Analyzed the use in newspaper headlines. Defined nationwide phraseological units and newspaper phraseological units headings.